ANTIDIABETIC ACTIVITY AND TOXICOLOGICAL EVALUATION OF THE METHANOL-DICHLOROMETHANE ROOT BARK EXTRACT OF NAUCLEA DIDERRICHII (DE WILD) MERR - Akunne, Theophine C.; Obi, Bonaventure C.; Ofokansi, Martha N.; Nwonu, Patience C.; Okoli, Charles O. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: In southeastern Nigeria, Nauclea diderrichii (De Wild) Merr is used in the treatment of a wide range of ailments including diabetes mellitus (DM). This study evaluates the antidiabetic activity and toxicological profile of the methanol-dichloromethane root bark extract of N. diderrichii in normoglycemic and alloxan-induced diabetic models. Methods: Dried root barks of N. diderrichii were extracted using methanol and dichloromethane (1:1) to obtain N. diderrichii extract (NDE). The acute and sub-chronic toxicity tests were performed using standard procedures. The effect on alanine aminotransferase (ALT) aspartate aminotransferase (AST), alkaline phosphatase (ALP), total protein (TP), packed cell volume (PCV), hemoglobin concentration (HB) and total white blood cell (TWBC) count was determined in the rats after treatment. In order to elucidate its antidiabetic mode of action, an oral glucose tolerance test (OGTT) was performed using glucose (2 g/kg) as substrate and alloxan (100 mg/kg; i. v.) induced diabetic model. Glibenclamide (GLI 0.2 mg/kg) was used as the reference standard drug. Results: The results indicated that the LD50 of the extract is>5000 mg/kg. ALT, AST, ALP PCV, HB and TWBC were insignificantly (p>0.05) different compared with the control. No significant changes were observed in the organ weights compared with the control. In the acute and prolonged antidiabetic study, NDE (100, 200 and 400 mg/kg) significantly reduced the blood glucose level (BGL) by 14.66, 18.9, 25.80% and 75.11, 80.24, 83.74% respectively. In comparison, GLI, when administered, reduced BGL by 38.18 and 92.86% respectively. Conclusion: N. diderrichii possesses antidiabetic activity with good toxicological profile.